Validated HPTLC Method for Accurate Measurement of Quercetin in Ficus benghalensis Linn. Bark Extract - Kumari, Sangita; Chopra, Mahendra Pratap (Indian Journal of Pharmaceutical Education and Research)
Background: Quercetin is a key bioactive compound found in many plants and trees, popularly known for its ability to act as a potent antioxidant, reduce inflammation, decreases the risk of cancer, heart disease, and neurological disorders, and even help with allergies and infections. The bark of Ficus benghalensis Linn. Commonly known as banyan tree is believed to be rich in quercetin, making its accurate measurement essential for understanding its health benefits. Purpose: This study focuses on determining the amount of quercetin in bark extract of Ficus benghalensis Linn. using a reliable High-Performance Thin Layer Chromatography (HPTLC) method. Materials and Methods: Chromatographic separation was performed on aluminum plates pre-coated with silica gel 60 F254 using a mobile phase of Toluene, Ethyl Acetate, Acetone, and Formic Acid in the ratio 5:2.5:7.5:0.5. The plates were scanned at 366 nm and 245 nm, providing a clear separation of Quercetin at a specific Retention Factor (Rf) A calibration curve was created, showing strong linearity with y = 8.6567x − 1357. The correlation coefficient (R2) was found to be 0.9985. The method also demonstrated a Detection Limit (LOD) of 75.60 ng/ spot and a Quantification Limit (LOQ) of 272.5 ng/spot. Results: The quercetin content in the bark was found to range from 1.99% to 24.48% w/w. The method proved to be sensitive as well as accurate and precise. Thus, it suitable for regular quality control. The developed method for high performance thin layer chromatography HPTLC was validated according to ICH guideline. Conclusion: This study successfully quantified quercetin in Ficus benghalensis Linn. bark using a validated HPTLC method. The approach is reliable for routine testing and highlights the potential of this medicinal plant for pharmaceutical and health applications.
Keywords: High-Performance Thin Layer Chromatography (HPTLC); Quercetin; Flavonoids; Ficus benghalensis Linn.; Accuracy; LOD; LOQ.